Will locality pay solve recruitment and retention problems in the federal civil service? - Lewis, Gregory B.; Durst, Samantha L. (1995)
The authors examine the logic underlying locality pay by testing hypotheses about recruitment and retention on a 1 percent sample of federal personnel records for 1985 through 1989. They find evidence that interarea differences in private sector pay levels have a limited impact on federal turnover rates, entry levels, promotion chances, or grade levels. Therefore, the Federal Employee Pay Comparability Act of 1990 (FEPCA) replaces a uniform national salary schedule for white-collar workers with a system of locality pay, which will remunerate the same work more highly in San Francisco than in Santa Fe.
Keywords: Civil service - U.S.A.